COMPORTAMENTO ECOLÓGICO DE TURISTAS E COMUNIDADE AUTÓCTONE: O CASO DO SALTO SÃO FRANCISCO-PR - Barby, Ricardo Luis (2015)
Studies focused on the relationship between human beings and the environment are given increasingly, dedication among scholars of different areas of knowledge featuring an interdisciplinary perspective. Likewise, observance of the behavioral phenomena of the human being in protected areas, in this case, involving tourism, they should take into account perspectives of both the tourist as the existing indigenous communities. In contemporary times it is observed break paradigms concerning environmental quality and social awareness to the issue. This work uses the Ecological Behavior Scale to measure the behavior of tourists and indigenous community of San Francisco Jumping on the Serra da Esperança. It was observed 20 participants tourists and 20 respondents community residents within a radius of 20 km from the attractive seat covering three counties of the State of Paraná. Of these 20 residents four of them have connection with tourism in generating family income. The results obtained through SPSS 18.0 software, and assertive applied Likert scale of 5 points, pointed to a pro-ecological behavior more responsible tourist in relation to the community, and more responsible for the individuals working with the tourism that those who do not perform economic activities involving tourism. The factors: energy and water savings, cleaning and recycling respondents had average values indicating responsibilities and the actions observed. On the issue of activism and consumption, none of the observed groups have demonstrated this characteristic.